Empowering negotiators - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
L Appui aux pays de l Afrique de l Ouest et du Centre face aux aspects agricoles des négociations multilatérales : Rapport d un atelier international, Dakar, Sénégal, 2000. Agricultural policy of African countries and multilateral trade negotiatio